Prevalence of diabetic retinopathy among self-reported adult diabetics in districts of Eastern Nepal in a community based study - Agarwal, Lalit T; Agrawal, Nisha (Nepalese Journal of Ophthalmology, 2018)
Introduction: Diabetic retinopathy (DR) is the leading cause of blindness among working age adults around the world. Each year more and more people live with this condition, which can result in life-changing complications. Objective: To determine the prevalence and risk factors of diabetic retinopathy (DR) in a large community based screening programme, in order to estimate the future burden of the disease. Materials and methods: A cross sectional community based study was conducted between 1st January and 31st December 2014 in a purposive sample of adults with selfreported diabetes mellitus (DM) from Morang and Sunsari district of Nepal. A structured questionnaire was used to collect patient data. Ophthalmological evaluation was done and fundus was examined for grading DR using direct and indirect ophthalmoscope. Results: Among the 698 diabetic patients, mean age was 55.02±11.8 years (ranging from 24 to 91 years). 12.3% of diabetic were not under any treatment. Only 69.3% of patients had visited eye specialist for diabetic retinopathy screening. Prevalence of DR was found to be 15.3%; 13.9% had non-proliferative DR and 1.4% had proliferative DR. Prevalence of diabetic macular edema was 2.1%. In Morang district prevalence of DR was 14.2% and in Sunsari district it was 16.2%. In the binary-logistic regression analysis, duration of diabetes was associated with significantly increased risk of DR (OR: 1.13; 95% confidence interval (CI), 1.09 to 1.17; p<0.001). History of absence of arterial hypertension decreased the risk of DR (OR: 0.56; 95% CI, 0.36 to 0.87; p=0.01). Conclusion: One sixth of the patients with diabetes in the Eastern region of Nepal have retinopathy. Diabetic retinopathy risk increased with duration of diabetes and decreased with history of no co-existing arterial hypertension.